ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE EOQ (ECONOMIC ORDER QUANTITY) UNTUK EFISIENSI PADA INDUSTRI BUMBU ROKOK (Studi CV. Pinuji Blitar, Jawa Timur) - Janggih Maqsuda; N. Rachma; M. khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACK               Raw material arrangements carried out by CV. Pinuji The procedure for purchasing cigarette raw materials will be made 40% of the needs of one month. Supervision, capacity in a storage warehouse of 20,000 kg. How to use (FIFO) raw materials first in first out, CV. Pinuji prepared Rp.21,660,000. (EOQ) economical order quantity The optimal number of clove handles is 21,398.50 kg each time ordering an order frequency 2 times with an optimal order time of 103 days, the total cost of one year is Rp.2,208,575. safety stock 222.13 kg. Reorder points 1649.85 kg Cost savings Rp.19,451,425 savings 89.80%.Keywords: Inventory control, raw materials, EOQ (economic order quantity), efficiency.